Long-time variations in leaf mass and area of Mediterranean evergreen broad-leaf and narrow-leaf maquis species - Gratani, L; Varone, L (Photosynthetica, 2006)
Morphological (dry mass, DM; surface area, LA; leaf mass per area, LMA), anatomical (leaf thickness, L), phenological (leaf life span, LL), and physiological (net photosynthetic rate, PN) leaf traits of the evergreen species co-occurring in the Mediterranean maquis developing at Castelporziano (Rome) were tested. The correlation analysis indicated that LMA variation was tightly associated with LL variations: Cistus incanus and Arbutus unedo had a short LL (4±1, summer leaves, and 11±1 months, respectively) and low LMA (153±19 g m –2 ) values, Quercus ilex, Phillyrea latifolia, and Pistacia lentiscus high LMA (204±7 g m –2 ) and long LL (22±3 months), Erica arborea, Erica multiflora, and Rosmarinus officinalis a short LL (9±2 months) and an either high (213±29 g m –2 , R. officinalis and E. multiflora) or low (115±17 g m –2 , E. arborea) LMA. LMA values were significantly (p≤0.05) correlated with PN (r≥0.68). In the tested species, LMA increased in response to the decrease of the total rainfall during the leaf expansion period. LMA variation was due to the unequal variation of DM and LA in the considered species. LMA is thus a good indicator of evergreen maquis species capability to respond to climate change, in particular to total rainfall decrease in the Mediterranean basin.
Keywords: dry mass; Erica; leaf life span; Leaf mass per area; Phillyrea; Pistacia; Quercus; RAINFALL; Rosmarinus.